THE EFFECT OF FIRM SIZE, SALES GROWTH AND PROFITABILITY ON COMPANY VALUE IN COMPANIES LISTED IN THE HEALTHCARE, TECHNOLOGY AND FOOD AND BEVERAGE SECTORS ON THE INDONESIA STOCK EXCHANGE: PENGARUH FIRM SIZE, SALES GROWTH DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR PADA SEKTOR HEALTHCARE, TEKNOLOGI SERTA MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Nanda Mutiara; Unggul Purwohedi; Sri Zulaihati (Yayasan Education and Social Center, 2022)
This study uses empirical evidence to confirm the impact of firm size, sales growth, and profitability on firm value. The data collection method used in this research is the documentation study method. The research approach used is quantitative. This study uses secondary data from the 2017-2020 financial statements Healthcare, Technology, and Food and Beverage Companies listed on the Indonesia Stock Exchange. Using the purposive sampling method, 37 samples were collected from a population of 120 companies comprising the study. The analytical techniques used are Multiple Linear Regression Analysis, Descriptive Statistics, Analysis Requirements Test (Normality Test and Linearity Test), Classical Assumption Test (Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test), Model Feasibility Test and Hypothesis Testing using SPSS version 25. Results The research shows that company size and sales growth have no effect on firm value, while profitability has a positive effect on firm value. To provide further research progress, namely to be able to expand other variables that affect the value of the company and increase the research period for the following year